THE IMPORTANCE OF RFID TECHNOLOGICAL SYSTEM - Azimov Jumanazar Turg‘unovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article, we have collected the main trends in the field of wireless communication for the present and the coming years. The latest innovations in the field of wireless communication, Radio Frequency Identification (RFID) the components, types, operating ranges, areas of application of the technological system, as well as existing problems and its role in society are covered in detail.